Instituições de longa permanência para idosos: um estudo de caso na cidade de Macapá - AP - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2019)
The Long Stay Institutions for the Elderly are usually linked and are researched by the health area, encompassing nursing, social assistance, physicians, meanwhile, little targeted by the architecture. In this sense, these institutions that shelter the elderly show a perspective that has not yet been explored, which is about their structure, their housing and their physical characteristics, so that they can attend to this social group adequately, within the parameters required by the Statute of the Elderly. With this, this work seeks to carry out a case study, through an analysis of the São José Abrigo space, in order to understand its functioning, its service and structuring as a space that should provide a good quality of life, to design a new environment which complies with current legislation. Thus, this work is subsidized by a specific scientific literature, which mainly guides the first and second chapter, in which a historical analysis is first made in conjunction with the constitution of the legislation around the ILPIs; in a second moment a reflection is made on the public policies focused on this segment, focusing on the shelters and their adequate training to give quality of life to the users of this institution. Therefore, in the third chapter, the analysis of the São José de Macapá Shelter is drawn, starting from a historical perspective and unraveling the space in question, in order to shape a new environment that contemplates the real needs of this social group.
Keywords: Instituição de Longa Permanência; Abrigos - Políticas públicas; Abrigo São José - Macapá (AP); CNPQ::CIENCIAS SOCIAIS APLICADAS